2010
DOI: 10.1002/ajmg.a.33783
|View full text |Cite
|
Sign up to set email alerts
|

Genotype–phenotype analysis of the branchio‐oculo‐facial syndrome

Abstract: Branchio-oculo-facial syndrome (BOFS; OMIM#113620) is a rare autosomal dominant craniofacial disorder with variable expression. Major features include cutaneous and ocular abnormalities, characteristic facies, renal, ectodermal, and temporal bone anomalies. Having determined that mutations involving TFAP2A result in BOFS, we studied a total of 30 families (41 affected individuals); 26/30 (87%) fulfilled our cardinal diagnostic criteria. The original family with the 3.2 Mb deletion including the TFAP2A gene rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(89 citation statements)
references
References 21 publications
3
80
0
6
Order By: Relevance
“…2E). To further validate AP-2α control of Girdin transcription, point mutations frequently observed in patients with branchio-oculo-facial syndrome (Milunsky et al, 2011), which are known to result in loss of AP-2α DNA binding (Garcia et al, 2000), were introduced into the basic region of human AP-2α expression plasmids. A reporter assay clearly indicated that these AP-2α point mutants failed to activate the Girdin promoter (Fig.…”
Section: Ap-2 Regulates Girdin Transcriptionmentioning
confidence: 99%
“…2E). To further validate AP-2α control of Girdin transcription, point mutations frequently observed in patients with branchio-oculo-facial syndrome (Milunsky et al, 2011), which are known to result in loss of AP-2α DNA binding (Garcia et al, 2000), were introduced into the basic region of human AP-2α expression plasmids. A reporter assay clearly indicated that these AP-2α point mutants failed to activate the Girdin promoter (Fig.…”
Section: Ap-2 Regulates Girdin Transcriptionmentioning
confidence: 99%
“…Il correspond à une anomalie du développement embryonnaire qui se traduit par des lésions cutanées caractéristiques associées à des atteintes oculaires et du massif cranio-facial. Les critères diagnostiques proposés par Milunski et al en 2010 [4] sont présentés dans le Tableau 1.…”
Section: Discussionunclassified
“…Lésion cutanée cervicale Anomalie oculaire Anomalie faciale Présence de deux critères majeurs associés à au moins un critère mineur parmi Un parent atteint au premier degré Présence dans le derme de cellules thymiques ectopiques D'après Milunski et al, 2010 [4].…”
Section: Présence Des Trois Critères Majeurs Suivantsunclassified
“…The cutaneous defects range from thin skin or a patch of hair to erythematous lesions. The majority of individuals diagnosed with BOFS carry a mutation in transcription factor TFAP2A [85]. TFAP2A is expressed during multiple stages of NCC development, including formation and migration, and has been shown to have roles in NCC specification [86].…”
Section: Branchio-oculo-facial Syndromementioning
confidence: 99%